Institutional Studies of Keureuto Watershed Water Resources Management as Disaster Mitigation - Dianto, Rinal; Azmeri, Azmeri; Yulianur, Alfiansyah (TDMRC, Universitas Syiah Kuala, 2024)
The Keureuto watershed is one of the priority watersheds in Aceh. The pressure on the Keureuto watershed is increasing due to climate change and regional growth. This watershed has the highest flood probability and victims in Aceh, reducing its water resources management effectiveness. This study aimed to examine the form and condition of the Keureuto watershed management institution and its future challenges. Data were collected using questionnaires administered to institutions and entrepreneurs directly involved in managing Keureuto watershed water resources. The data were then analyzed using the SWOT model. The parameters examined include operation patterns, management, and perceptions of individuals involved in regional development and the water sector. The results of the analysis show that budget availability and coordination between stakeholders influence water resources management in the Keureuto watershed. The problems in the Keureuto watershed can be addressed by establishing a particular management body under the ministry or by strengthening existing institutions' authority. The new institution takes the form of an Otorita (a legal entity authorized to conduct business by Presidential Decree) or a particular management agency. The authority needed by the Keureuto watershed management is in budgeting flexibility and the authority to carry out infrastructure activities before and after flooding.